Adapting cooperative learning (jigsaw) in teaching - A. Aziz, Mohd Norafizal; Hashim, Hasnizawati; A. Halid, Rozieana (2009)
Implementing cooperative learning in teaching is one of the many teaching concepts that can be used by the educator in teaching and learning process at every level of education. This paper will stress on the importance of cooperative teaching methodology and how it can be used in the classroom. A few examples will be explained in detail in implementing this approach successfully so that it could become a guideline to the lecturers to suit with the subjects taught by them. It is hoped that this paper will bring more benefits not only to the lecturers, but also to the students as well to improve the teaching skills and enhancing the knowledge delivering process in the classroom.